Difference of quaternionic weighted composition operators on slice regular Fock spaces. Issue 1 (2nd January 2023) - Liang, Y.; Wang, J.
Abstract : Quaternionic Fock space is a useful generalization of the Fock space in the complex plane, which plays an important role in quantum mechanics. In view of quaternionic operator theory this topic attains more diversity and complexity. In this paper we first explore the connection between the properties and about the difference of quaternionic weighted composition operators acting on slice regular Fock space with the function theoretic properties of the symbols. It can further imply some topological information on the set of quaternionic weighted composition operators.